2015
DOI: 10.1186/s12889-015-2189-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study

Abstract: BackgroundUnderstanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour.MethodsDietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 51 publications
7
49
1
1
Order By: Relevance
“…These differences could be explained by a greater concern for physical appearance and weight control in girls. In a longitudinal study did in German, girls showed a decrease in meat intake and increase in whole and refined grains, vegetables, oils and tea intake with puberty onset; however, boys tended to keep a similar diet when reaching puberty [33]. Swedish Females from 17 to 21, also ate fruit and drank tea more often than males [34].…”
Section: Discussionmentioning
confidence: 96%
“…These differences could be explained by a greater concern for physical appearance and weight control in girls. In a longitudinal study did in German, girls showed a decrease in meat intake and increase in whole and refined grains, vegetables, oils and tea intake with puberty onset; however, boys tended to keep a similar diet when reaching puberty [33]. Swedish Females from 17 to 21, also ate fruit and drank tea more often than males [34].…”
Section: Discussionmentioning
confidence: 96%
“…The other 14 studies (17 reports) were 258 considered of lower quality (41,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) . 260 The "vegetable" group was not defined in most reports (50,54,(56)(57)(58) ; in others (49,55) , it was composed 261 of raw, frozen, canned and cooked vegetables. The "fruit" group composition was less 262 homogeneous: some included 100% fruit juice (56) , all types of fruit juice (58) , dried fruits (56) or only 263 fresh (49) or whole fruits (57) , while some did not define composition (50,54,55) .…”
mentioning
confidence: 99%
“…Information on food intake over the past 12 months was obtained at each follow-up. The FFQs were filled predominantly by the parents at 10-year follow-up, and by the subjects with the help of parent at 15year follow-up [18]. After quality control, the collected data were classified into 17 major food groups or 41 subgroups.…”
Section: Questionnairementioning
confidence: 99%
“…After quality control, the collected data were classified into 17 major food groups or 41 subgroups. Intake in g/day was calculated from the reported frequency of intake and estimated portion sizes Details on the quality control procedure and grouping can be found in a previously published article [18]. The SSD subgroup included colas, lemonades, ice-tea, sport/energy drinks, fruit squashes and nectars.…”
Section: Questionnairementioning
confidence: 99%